2022
DOI: 10.3390/land12010063
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Gross Ecosystem Product and Analysis of the Transformation Path of “Two Mountains” in Hulunbuir City, China

Abstract: The objective assessment of ecological systems forms the basis of solving ecological environmental problems. Evaluating the ecosystem status of each county through the gross ecosystem product (GEP) can reveal the value of each ecosystem. In this study, we used the eco-economic method to calculate the GEP and the green gold index (GGI) of 13 counties in Hulunbuir City between 2015 and 2020. The results show that: (1) The GEP of Hulunbuir City in 2020 was 980.025 billion yuan. The GGI was 8.36, which was much hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…We found that this is related to the distribution characteristics of land use types and ecosystem types. This is consistent with the findings of Wang et al [57] and Zhou et al [58]. In response to the following results, we make several suggestions for the sustainable development of Fujian Province.…”
Section: Sustainable Development Recommendations For the Study Areasupporting
confidence: 93%
“…We found that this is related to the distribution characteristics of land use types and ecosystem types. This is consistent with the findings of Wang et al [57] and Zhou et al [58]. In response to the following results, we make several suggestions for the sustainable development of Fujian Province.…”
Section: Sustainable Development Recommendations For the Study Areasupporting
confidence: 93%
“…GEP can contribute to achieving important societal objectives, such as sustainable development, by bringing the value of ecosystem services and trends in ecosystem assets into public and private sector decision making and investment planning. The GEP accounting results of IMAR showed that the value of ecosystem services in IMAR area gradually increased between 2000 and 2020, which is consistent with the findings of Na et al (2022) and Zhao et al (2023).…”
Section: Gep Work In Parallel With Gdpsupporting
confidence: 82%
“…GEP is the sum of the economic value of final goods and services provided by ecosystems for economic and social development [28]. On the basis of the technical guidelines of GEP [29] and the characteristics of the Tuojiang River Basin, this study established a GEP accounting system, shown in Figure 2. This system is constituted of three hierarchies, including products, regulating services, and cultural services.…”
Section: Ecp and Ecr Identificationmentioning
confidence: 99%